Mothers’ Experience in Caring Children with Nephropatic Syndrome during Relapse: A Phenomenological Study - Yelly Herien; Indria Laksmi Gamayanti; Intansari Nurjannah (Alta Dharma Publisher, 2020)
Nephrotic syndrome is a disease with a high relapse prevalence in children. This relapse could force the children to be hospitalized, causing physical and behavioral changes in the children, and disturbing psychological stability and daily activities of family members, particularly mothers. The study aimed to explore mother experience in caring for her child during relapse and the value of the experience. This was a qualitative study with a phenomenology approach. Respondents were six mothers of children who had been diagnosed with the nephrotic syndrome for more than one year and had a relapse in the last year. A purposive sampling method was used to select the participants. The main instrument was the author. Data collection was conducted with an in-depth interview, observation, and field notes. Data analysis used Colaizzi's method. Data was collected from interview results, turned to a transcript, classified, and sub-themes and themes were determined. This study showed six themes, which were Inadequate Knowledge of Nephrotic Syndrome, Being Worried about Child's Condition, Physical Changes During Relapse, Caring Children During Relapse, Concern About Social Support and Challenges in Caring. Various treatments for their children were conducted by mothers, including home treatment, using modern medicine in the hospital, and alternative treatment. Mothers require support from multiple sources to deal with the difficulties that they have in the children's treatment